Purchasing patterns of the hotel sector in the Bahamas, Barbados, Belize, Jamaica and Trinidad and Tobago (CEDP St. Michael, BarbadosBB, 1992)
Examines the hotel sector in the countries of study and identifies opportunities for increased consumption of local and regional products within that sector. Describes policies and practices in the acquisition and consumption of goods by the hotel sector. Recommends quality improvement, establishment of industry standards and competitive pricing as means of increasing levels of purchasing of local and regional products. Outlines strategic approach in the development of a plan of action to increase usage of regional products by the hotel sector.
DC